One-step Purification of Twin-Strep-tagged Proteins and Their Complexes on Strep-Tactin Resin Cross-linked With Bis(sulfosuccinimidyl) Suberate (BS3) - Ivanov, Konstantin I (MyJove Corporation, 2014)
Affinity purification of Strep-tagged fusion proteins on resins carrying an engineered streptavidin (Strep-Tactin) has become a widely used method for isolation of protein complexes under physiological conditions. Fusion proteins containing two copies of Strep-tag II, designated twin-Strep-tag or SIII-tag, have the advantage of higher affinity for Strep-Tactin compared to those containing only a single Strep-tag, thus allowing more efficient protein purification. However, this advantage is offset by the fact that elution of twin-Strep-tagged proteins with biotin may be incomplete, leading to low protein recovery. The recovery can be dramatically improved by using denaturing elution with sodium dodecyl sulfate (SDS), but this leads to sample contamination with Strep-Tactin released from the resin, making the assay incompatible with downstream proteomic analysis. To overcome this limitation, we have developed a method whereby resin-coupled tetramer of Strep-Tactin is first stabilized by covalent cross-linking with Bis(sulfosuccinimidyl) suberate (BS3) and the resulting cross-linked resin is then used to purify target protein complexes in a single batch purification step. Efficient elution with SDS ensures good protein recovery, while the absence of contaminating Strep-Tactin allows downstream protein analysis by mass spectrometry. As a proof of concept, we describe here a protocol for purification of SIII-tagged viral protein VPg-Pro from nuclei of virus-infected N. benthamiana plants using the Strep-Tactin polymethacrylate resin cross-linked with BS3. The same protocol can be used to purify any twin-Strep-tagged protein of interest and characterize its physiological binding partners.